Outcome of Lymph Node Biopsy in Gulab Devi Chest Hospital - ZAHEER AKHTAR**, GHULAM SHABBIR PERVAIZ, HAMID HASSSAN (Journal of Fatima Jinnah Medical University, 2018)
Background: Lymph node biopsy is a diagnostic procedure done in lymphadenopathy. Lymphadenopathy is an abnormal increase in size of lymph nodes which may be due to infection, inflammation, malignancyand many other diseases. Objective: To see the histopathological outcome of lymph node biopsy and to see the sensitivity and specificity of lymph node biopsy in Tuberculosis and malignancy. Methods: 212 patients with lymph node enlargement who had lymph node biopsies at the Gulab Devi hospital Lahore in 2012. The clinical parameters age, fever, and weight loss were measured at initial examination. Fine needle aspiration cytology was done in all patients. The patients were divided into 4 groups 1st Tuberculous, 2nd cancerous, 3rd specific reactive hyperplasia and 4th one is tuberculous abscess. These groups were compared based on patient’s clinical parameters. Biopsies were taken from different area of cervical, supraclavicalar, axillaries, and submendibular and mediastinal lymph nodes depending upon area involved. Results: Out of 212 patients, 148(69.81%) presented with cervical, 34(16.03%) were presented with supraclavicular, 19(8.96%) were presented with axillary, 6(2.83%) were presented with submendibular lymphadenopathy. Only 5(2.35%) cases of mediastinal lymphadenopathy were reported. The final diagnosis indicated that the patient had Tuberculosis (132; 62.25%), 60(28.30%) had cancer and 20(9.43%) had nonspecific reactive hyperplasia. Conclusion: Tuberculous lymphadenitis (62.25%) represented the commonest infectious etiology in our study and malignancy (28.30%)was the second major cause. Therefore histological proof is necessary in suspected case of lymhadenopathy.